In Silico drug evaluation by molecular docking, ADME studies and DFT calculations of 2-(6-chloro-2-(4-chlorophenyl)imidazo[1,2-a]pyridin-3-yl)-N, N-dipropylacetamide - Tahiroglu, Veysel; Goren, Kenan; Baglan, Mehmet (BMC, 2025)
In this study, the structural, electronic, pharmacokinetic, and biological properties of molecule 2-(6-kloro-2-(4-klorofenil)imidazo[1,2-a]piridin-3-il)-N, N-dipropilasetamid (Alpidem), an imidazopyridine derivative anxiolytic known for its high BZ(1) (benzodiazepine-1) receptor affinity and low adverse effect profile, were comprehensively investigated by density functional theory (DFT) and in-silico methods. The alpidem molecule was optimized using the 6-311G(d, p) basis set with the B3LYP and B3PW91 methods; information on the stability and chemical reactivity of the structure was obtained via the highest occupied molecular orbital (HOMO), lowest unoccupied molecular orbital (LUMO), molecular electrostatic potential (MEP) maps, natural bonding orbital (NBO) analysis, non-linear optical (NLO) properties, and Mulliken charge distributions. Comparative analysis of two different methods has shown that the results are consistent with each other and provide reliable data. In addition, the drug similarity, bioavailability score, bioactivity values, absorption, distribution, metabolism, and excretion (ADME) profiles of the Alpidem molecule were calculated, and it was determined that the Alpidem molecule has pharmacologically favorable properties. Within the scope of molecular docking analyses, its interactions with two different enzymes (PDB ID: 2Z5X and 4BDT) associated with Alzheimer's disease were evaluated. The binding energy values obtained were - 8.00 kcal/mol (2Z5X) and - 9.60 kcal/mol (4BDT), respectively, and the strong binding affinity, especially with the 4BDT protein, suggests that Alpidem may be a potential inhibitor candidate in Alzheimer's disease. This multi-level theoretical study demonstrates that Alpidem is a drug repurposing molecule not only as an anxiolytic but also in neurodegenerative diseases and provides important data that will shed light on experimental studies. The results of this multi-level theoretical study show that Alpidem is a drug repurposing molecule not only as an anxiolytic but also in neurodegenerative diseases and provides important data that will shed light on experimental studies.
Keywords: DFT; Moleculer docking; HOMO-LUMO; NLO; NBO; ADME; Mulliken charges; Alpidem